Creative Destruction, Social Security Uptake and Union Networks - Harald Dale-Olsen (Institute of Labor Economics (IZA), 2019)
Does the creative destruction induced by unions entail increased social security uptake? Creative destruction implies the closures of less productive workplaces, and if the regional benefits from this process is not large enough, the displacements caused by workplace closures cause increased social security uptake. In this paper we apply a shift-share approach and historical unionisation data from 1918 to study the impact of regional unionisation changes in Norway on regional social security uptake during the period 2003-2012. As regional unionisation increases, inflows to regional unemployment and disability decrease, but the outflow to retirement increases.
Keywords: D24; J30; J51; 330; trade unions; creative destruction; unemployment; disability insurance; retirement